1980
DOI: 10.1111/j.1432-1033.1980.tb04710.x
|View full text |Cite
|
Sign up to set email alerts
|

Labelling in vivo and in vitro of Molecular Species of Lipids from Chloroplast Envelopes and Thylakoids

Abstract: Lipid mixtures from chloroplast envelope and thylakoid membranes were isolated after different labelling times in vivo and in vitro and separated into major components. The isolated compounds were subjected to analyses such as separation of molecular species, determination of radioactivity in fatty acids and water-soluble hydrolysis products and radio gas-liquid chromatography of fatty acid mixtures. In the case of monogalactosyl and digalactosyl diacylglycerol these procedures were also applied to several ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…In agreement with previous findings (26,27), the treatment of detached leaves with ['4C]acetate resulted in a high MGDG labeling, but in low DGDG labeling. After 2 h of incubation, 30% of the radioactivity recovered from total acyl lipids was found in MGDG, but only 3% in DGDG (Table II).…”
Section: Formation and Desaturation Of Prokaryotic Galactolipids In Dsupporting
confidence: 81%
“…In agreement with previous findings (26,27), the treatment of detached leaves with ['4C]acetate resulted in a high MGDG labeling, but in low DGDG labeling. After 2 h of incubation, 30% of the radioactivity recovered from total acyl lipids was found in MGDG, but only 3% in DGDG (Table II).…”
Section: Formation and Desaturation Of Prokaryotic Galactolipids In Dsupporting
confidence: 81%
“…The free fatty acids synthesized by isolated chloroplasts, which consisted of 75 to 80%o oleic acid, were 66% converted to [14Clacyl-CoAs in the presence of exogenous CoA and ATP (20) and have been considered to be the most likely precursors for PC synthesis in vivo (17,19). This high oleic acid content of the free fatty acid fraction and its derivative acyl-CoA is in marked contrast with the fatty acid disposition of l-oleoyl-2-palmitoyl or 1,2-dipalmitoyl found both in the precursor diacylglycerols synthesized in vitro (10,17) and the DGG and PG derived from them in vivo (15,17,23,29 (Table I). Low DGG and SL labeling and high PC labeling was found in pumpkin, sunflower, and broad bean, whereas higher labeling of DGG and SL and lower PC labeling was found in tomato, parsley, and spinach.…”
mentioning
confidence: 79%
“…Chromoplast membranes from N. pseudonarcissus were prepared by disrupting the organelles with a tight-fitting Potter homogenizer in a medium containing 25 mM Tricine and 5 mM 2-mercaptoethanol (pH 7.6 with KOH). Total chromoplast membranes were then collected by centrifugation at l00,O00gmax for 2 h (4°C).…”
Section: Plastid Membranesmentioning
confidence: 99%
“…In 16:3 plants, the two galactolipids MGDG and DGDG are present in both the prokaryotic and eukaryotic configuration (3,16,20), and thus must be derived partially from plastid and partially from reticular diacylglycerol residues. The galactolipids of 18:3 plants, however, are found only in the eukaryotic configuration.In the membranes of chloroplasts and other plastids, MGDG and DGDG are formed by stepwise galactosylation of diacylglycerol (7,21,25,29). It has been suggested that pro-and eukaryotic galactolipid molecules might be synthesized in plastids by different sets of enzymes, the prokaryotic galactolipids being formed in the inner and eukaryotic lipids in the outer envelope membrane (2, 3,17,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation